Translation as intervention: Sambhu Mitra’s Putul Khela (A doll’s house) - Ahsanuzzaman, Ahmed (Nordlit, 2015)
For post-colonial writers and theorists, translation is a highly political activity. As Susan Bassnett and Harish Trivedi say, “translation is a highly manipulative activity” and it “involves all kinds of stages in ... [the] process of [“intercultural”] transfer across linguistic and cultural boundaries” (1999, 2). They hold that the “the common translatorial temptation [is] to erase much that is culturally specific, to sanitize much that is comparatively odorous” (ibid). Rustom Bharucha terms translation as “intervention”. This article considers the Bengali translation of Ibsen’s A Doll’s House in 1958 by one of India’s theatre legends, Sambhu Mitra (1915-1997). The paper reads Mitra’s translation as “intervention”, studying it at the linguistic level. It contends that Mitra pronounces his voice by intervening in the translation through making careful choices which include, among other issues, his choice of the title as well as his handling of Ibsen’s swear-words and special words.